Balanced Scorecard in Business Performance Measurement and its Effect on Financial Structure (Global Journal of Management and Business Research, 2018)
An effective performance appraisal system is substantially important for the success of the enterprises competing in complex environments. Performance measures are used in the evaluation, control and development of the enterprises’ processes to ensure achieving their goals and objectives. Performance measures are also used to compare the performance of different enterprises, factories, departments, teams, and individuals. Traditional performance appraisal methods based on financial criteria have been widely used in assessing business performance. However, performance evaluation methods, which are based on only financial criteria, are not enough to evaluate the performances of the enterprises today. Recognizing the incomplete aspects of performance measures based on financial measures, has led to the emergence of multidimensional performance appraisal approaches in assessing organizational performance. Therefore, along with the financial perspective, enterprises should also consider other perspectives while designing performance appraisal systems. The Balanced scorecard method is one of the multidimensional performance evaluation methods used in evaluating organizational performance. In this study; first, the concept of performance is explained with the main lines, and among the multidimensional performance evaluation methods, the balanced scorecard method is discussed. In the sequel, the methods used for evaluating the enterprises’ financial structures are given. Finally, an analysis is carried out on the financial structure state and the resulting changes of a medium-sized industrial enterprise before and after the application of the balanced scorecard.
Keywords: performance measurement; balanced scorecard; financial structure